EVALUASI EFEK SAMPING ANTIRETROVIRAL PADA PASIEN HIV/AIDS DI RSUP Dr. SARDJITO YOGYAKARTA PERIODE TAHUN 2009-2013 - , EKKY SABRINA DIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Side effects likely to occur in the use of drugs is no exception antiretroviral (ARV) as an option of therapy in HIV/AIDS. Side effects that occurred in antiretroviral use may result in reduced patient compliance in taking medication so that the expected therapeutic outcomes will not be achieved. This study was conducted to determine the type of side effects and the managements which are conducted on the side effects of antiretroviral on HIV/AIDS patients in RSUP Dr. Sardjito Yogyakarta year period from 2009 to 2013. This study used a cross-sectional research design and the datas were collected retrospectively from patients' medical record files who meet the inclusions and exclusions criteria. The datas were analyzed descriptively and compared with the National Guidelines of Clinical Management of HIV Infection and Antiretroviral Therapy by Indonesian Department of Health in 2011. The results showed from 121 patients, 102 patients (84.30%) had received antiretroviral therapy that in accordance with national guidelines of HIV/AIDS treatment, with 68 patients (56.20%) of them using AZT+3TC+NVP as a combination of antiretroviral regimen. There are 92 patients (76.03%) experienced adverse events and the most common types of ARV side effects is itching, which is 31 cases (25.62%). Most patients received adjunctive therapy for the treatment of side effects, which occurred in 135 cases of additional therapy. There are 55 patients (45.45%) who experienced substitution of ARV regimens and in accordance with guidelines. The success of the treatment of the side effects occur in all patients that were shown by the absence of complaints and the results of laboratory tests showed normal numbers.